Ocena natančnosti satelitske navigacije pri upravljanju naravnih virov - Hengl, Tomislav (Strojniški vestnik, 2006)
This article deals with the possibilities of applying GPS navigation technology to the management of natural resources. It is based on the results of GPS soil mapping at about 30 locations in Baranja (eastern Croatia). The GPS receivers were used primarily for the positioning of the soil-sampling sites. Dynamic mapping was not monitored. The practical purpose of the research was to learn more about working with GPS data, integrating GPS into geographic information system (GIS), and testing the possibilities of the moreprecise Differential GPS (DGPS). The differences between the data obtainedusing three methods of point positioning in space were testedČ a) geo-referenced aerial photographs (AERO), b) a standard GPS signal, and c) a corrected DGPS signal. A systematic deviation and an error radius were established with respect to the reference value (the DGPS results). Testing the difference between the GPS and AERO did not show any statistically significant difference between these two methods. According to the results of the research, GPS positioning can be successfully applied to soil mapping and to natural-resource inventories in general. Positioning with an uncorrected GPS signal provides equal or better positioning accuracy than that obtained from aerial photographs at an approximate scale of 1:20,000. The use of satellite positioning depends on the needs of a given user group, where aspects relating to precision, a 95% probability radius, the reliability of results and the feasibility are of particular importance.
Keywords: navigacija satelitska; satelitsko določanje lege; kmetijstvo usmerjeno; upravljanje z gozdovi; ocena natančnosti; satelitska navigacija; GPS; gospodarjenje z gozdovi